THE PATTERN OF STUDENTS' CHARACTER COACHING IN ANTICIPATING INTOLERANCE BELIEF IN ISLAMIC RELIGIOUS UNIVERSITIES IN SULAWESI BARAT - Muliadi Muliadi; A. Zamakhsyari Baharuddin (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
This study aimed to determine the role of Islamic Religious Universities (PTKI) in West Sulawesi in establishing the character as an effort in student coaching to anticipate intolerance belief and radicalism. The research type and method used was qualitative. This research is expected to be able to provide a systematic, thorough, and accurate description of the pattern of students coaching at PTKI in counteracting the radicalism in West Sulawesi. The data generated in this study are presented in a descriptive form. The research was conducted in 4 (four) PTKI namely STAIN Majene, STAIN DDI Majene, STAI Al-Azhary Mamuju, and IAI DDI Polman. The results showed that the strategy of students' character coaching of PTKI in West Sulawesi as an effort to anticipate the intolerant belief and radicalism refers to the Marten strategy which includes 3 (three) stages, namely: the identify the values, teach the values, and apply the values. In practice, the strategy which was implemented integratedly could successfully create a pattern of coaching in the form of training, consulting, mentoring, managing, and leading under the synergogy concept which leads to the strengthening of the national knowledge and the deepening the religious understanding.